Effects of Pilot Injection Timing and EGR on a Modern V6 Common Rail Direct Injection Diesel Engine - Nik Rosli, Abdullah; R., Mamat; Wyszynski, Miroslaw L.; Tsolakis, Anthanasios; Xu, Hongming (IOP Publishing, 2013)
Nitric oxide and smoke emissions in diesel engine can be controlled by optimising the air/fuel mixture and combustion temperature. Early in-cylinder diesel injection that produces premixed charge can simultaneously reduce NOx and smoke emissions. However, there could be an increase in hydrocarbons and CO emissions due to fuel impinged to the cylinder wall. The focus of the present work is on the effects of a variation of pilot injection timing with EGR to NOx and smoke level of a modern V6 common rail direct injection. This study is carried out at two different engine load conditions of 30 Nm and 55 Nm, at constant engine speed of 2000 rpm. Emissions of NOx are measured from the exhaust sample line by an exhaust gas analyzer (Horiba MEXA-7100EGR). Smoke level is measured by using an AVL 415S smoke meter which provides results directly as a Filter Smoke Number (FSN) unit. The results show that the early pilot injection timing contributed to the lower smoke level and higher NOx emissions. The higher level of NOx is due to higher combustion temperatures resulting from the complete combustion. Meanwhile, the lower smoke level is due to complete fuel combustion and soot oxidation. The early pilot injection timing produces an intermediate main ignition delay which also contributed to complete combustion. The formation of smoke is higher at a high engine load compared with low engine load is due to the higher amount of fuel being injected, resulting in higher smoke formation